Pembuatan Bibliografi Beranotasi Koleksi Bahan Ajar di Perpustakaan Politeknik Akademi Teknologi Industri Padang - Mardyisa, Ega; Desriyeni, Desriyeni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2017)
This paper discusses the Making of Annotated Bibliography of Teaching Materials Collection at Padang Industrial Technology Academy Library. The purpose of this paper is to describe the making of annotated collection of teaching materialsBibliography at the Library of Industrial Technology Academy of Padang. The method used was descriptive method which technique of data collectionwere through direct observation or observation. The observations were conducted directly by investigating and recording the collection of teaching materials at the Padang Industrial Technology Academy Library. The results obtained in direct observation, the amount of collection of teaching materials at the Padang Industrial Academy Library was 59 titles with a total of 102 copies. Based on the discussion, It concluded that the compilation of bibliography annotated collection of teaching materials at the Polytechnic Library of Industrial Technology Academy of Padang done through the several stages. First, determines the bibliographic titles. Second, collects the library materials or investigates bibliographic information on the collection of teaching materials. Third, selects library materials.Fourth, groups or classifies annotated bibliography of the collection of teaching materials based on the content and the subject. Fifth,generates the keyword. Sixth, indexes the bibliographic collection of teaching materials. Seventh, types the manuscript bibliography. The final stage in making a bibliography of annotated teaching materials collection was the final manuscript examination. Keyword: bliography, teaching materials.